Child Maltreatment and Adolescents' Exposure to Disorder in Daily Activity Spaces. - Yoon, Susan; Yang, Junyeong; Napier, Taylor; Wang, Jingyi; Maguire-Jack, Kathryn; Boettner, Bethany; Browning, Christopher R. (Journal of Youth & Adolescence, 2026)
Minimal research has explored how child maltreatment shapes adolescents' exposure to risky environments within youth activity spaces (the places youth visit during their daily routine) which likely influences youth well-being. This study examined the extent to which child maltreatment and neighborhood disorder, individually and collectively, are associated with adolescents' exposure to physical and social disorder in their activity spaces. Participants were 1215 adolescents (47% boys, M = 14.26, SD = 1.87) recruited from a Midwestern city in the United States. Multilevel modeling was conducted. The results indicated a positive association between child maltreatment and disordered activity spaces, with no significant moderation by residential neighborhood-level disorder. The findings point to the need for enhanced maltreatment prevention efforts and targeted interventions to mitigate environmental risks for adolescents with maltreatment histories.